Ruin, Resistance and Resilience: a cartography of the Costa da Conceição Lagoa in Florianópolis – SC - Freitas, Djonathan; Fiorin, Evandro (National Journal of City Management, 2022)
This major interest of this research is to demonstrate the historical, cultural and environmental importance of the path of the Lagoa da Conceição Coast, in Florianópolis, Santa Catarina. The route is little studied by historiography and intends to reveal another look at the community that inhabits this region of difficult access in the island landscape, as well as the cultural heritage still existing there. For this, surveys were conducted about the history of occupation of the region, mainly in the face of the transformations of current ways of life, seeking to highlight its cultural traits, which still preserve remnants of the former Azorean immigrants. Thus, through walking as an aesthetic practice, in the search for an encounter with the Other, we investigate what we call here the path of the ruins, that is, some abandoned architectures along the Coast of Lagoa da Conceição, emphasizing the importance for the construction of identities and the need for permanence, without an architectural rejuvenationAs results, we elaborated a discussion about the relevance of this heritage and its cultural landscape in view of the concepts and processes of perception that reveal the surprises of these ruins as resistance and resilience of this place for the constitution of promontory of desires.